2016
DOI: 10.1007/s12185-016-2028-9
|View full text |Cite
|
Sign up to set email alerts
|

High IL-7 levels in the bone marrow microenvironment mediate imatinib resistance and predict disease progression in chronic myeloid leukemia

Abstract: Chronic myeloid leukemia (CML) is a three-stage myeloproliferative disease caused by translocation between chromosomes 9 and 22. Although tyrosine kinase inhibitors (TKI) are highly effective in the treatment of CML, numerous clinical trials have shown that many patients become refractory or drug resistance, especially those in the blastic crisis of CML. The molecular mechanisms underlying CML, however, remain poorly understood. In the present study, we used a coculture model to address possible mechanisms und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…However, recent evidence shows that IL-7 promotes DNA synthesis in leukemia cells. Zhang and colleagues [169] identified a source of IL-7 in MSCs that secretes high levels of this cytokine to protect leukemic cells against apoptosis induced by Imatinib or Gleevec, a potent tyrosine kinase inhibitor. Of particular interest was another report showing that fatty acids produced by MSCs help cancer cells to survive after platinum-based chemotherapy (Cisplatin) [170].…”
Section: Mscs and Cancer Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent evidence shows that IL-7 promotes DNA synthesis in leukemia cells. Zhang and colleagues [169] identified a source of IL-7 in MSCs that secretes high levels of this cytokine to protect leukemic cells against apoptosis induced by Imatinib or Gleevec, a potent tyrosine kinase inhibitor. Of particular interest was another report showing that fatty acids produced by MSCs help cancer cells to survive after platinum-based chemotherapy (Cisplatin) [170].…”
Section: Mscs and Cancer Cellsmentioning
confidence: 99%
“…MSCs' contribution to cancer survival is very similar to their role in tissue regeneration and maintenance of normal SCs niches [136, 173]. Among other cancer survival strategies, the TME promotes the generation of CSCs which in turn can actively educate their surroundings through interactions with other SCs (like MSCs) to guarantee self-renewal states and to give rise to the subsequent production of aggressive cells [169, 174]. Thus, MSCs' stemness-related properties, plasticity, and the ability to sustain tissue repair should be further studied in order to effectively target their cancer-supporting pathways in the TME.…”
Section: Mscs and Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…These drugs have potent anti-proliferative effect, potentiate TKI effect, reducing adhesion of neoplastic cells to BM stroma and increasing apoptotic ability, on the long run there was a noticed decrease in prevalence of IM resistance and achieving optimal molecular response in previously resistant patients. 24,25 Our current study could suggest that addition of drugs that antagonize IL-7 may aid in modifying disease progression and help in cases resistant to IM therapy. This could be confirmed by data from Zhang and his colleagues, who reported that high IL-7 in bone marrow mediates imatinib resistance, and targeting IL-7 pathway is a promising approach in CML therapy.…”
Section: Discussionmentioning
confidence: 90%
“…The chemoprotective effect of the BM microenvironment has been shown using in vitro CML cellular models under IM treatment . For example, cytokines within the BM microenvironment, such as interleukin (IL)‐3, IL‐7, granulocyte‐macrophage colony‐stimulating factor, and C‐X‐C motif chemokine 12, can protect CML cells from IM‐induced apoptosis and promote CML cell survival . However, it remains unknown whether there are other soluble factors that are chemoprotective for CML cells under IM treatment.…”
Section: Introductionmentioning
confidence: 99%